The Hydraenidae of Cuba (Insecta: Coleoptera) III. Description of two new hygropetric species of Hydraena Kugelann - Deler-Hernández, Albert; Fikáček, Martin; Delgado, Juan A. (Zootaxa, 2017)
Two new species of the genus Hydraena Kugelann, 1794 collected from hygropetric habitats in eastern Cuba are described: Hydraena (Hydraenopsis) blancae sp. nov. from the Nipe-Sagua-Baracoa mountain range, and Hydraena (Hydraenopsis) matthiasi sp. nov. from the Sierra Maestra mountain range. Both species, especially the latter, are closely related to Hydraena (Hydraenopsis) franklyni Deler-Hernández & Delgado, 2012. Diagnostic characters for both new species are provided and illustrated; habitat information and distributional data are also included. An updated key to Cuban species of Hydraena is provided. With this study, the number of species of Hydraena known from Cuba raises to six.